2016
DOI: 10.1111/pcmr.12504
|View full text |Cite
|
Sign up to set email alerts
|

Simple chronic colitis model using hypopigmented mice with a Hermansky–Pudlak syndrome 5 gene mutation

Abstract: Pigmentation in mammals is important for protection of skin and eyes from ultraviolet radiation. Dysregulation of pigmentation is often associated with other conditions that are not directly linked to pigmentation. Here, we isolated spontaneously occurring hypopigmented mice that occasionally experienced severe diarrhea during lactation. Treatment of these mice with dextran sulfate sodium salt, a conventional method to induce acute colitis, caused chronic diarrhea with granulomatous colitis. Gene mapping and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…We previously reported that hypopigmented mice with Hps5 gene deficiency, ruby-eye 2 (ru2), tended to develop colitis [17], while patients with HPS1 and HPS4 also developed granulomatous colitis [16]. However, only a few patients with HPS5, as well as HPS3, have experienced similar gastrointestinal symptoms [2,12,13,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that hypopigmented mice with Hps5 gene deficiency, ruby-eye 2 (ru2), tended to develop colitis [17], while patients with HPS1 and HPS4 also developed granulomatous colitis [16]. However, only a few patients with HPS5, as well as HPS3, have experienced similar gastrointestinal symptoms [2,12,13,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%